Effect of Diamond-Like Carbon Coatings on Ball Bearing Performance in Normal, Oil-Starved, and Debris-Damaged Conditions. Issue 6 (1st November 2016) - Mutyala, Kalyan C.; Singh, Harpal; Evans, R. D.; Doll, G. L.
ABSTRACT: In this study, a process was developed to deposit wear-resistant metal-doped diamond-like amorphous hydrocarbon and carbon coatings onto spherical rolling elements. Nanocomposite WC/a-C:H, TiC/a-C, and Ti/a-C:H coatings were applied in a closed-field unbalanced magnetron sputtering system and their mechanical, compositional, and microstructural properties were examined. The ability of the coated spherical rolling elements to affect bearing performance in normal, oil-starved, and debris-damaged conditions was evaluated in thrust bearing tests. WC/a-C:H-coated spherical rolling elements (balls) exhibit the ability to improve bearing performance in normal, oil-starved, and debris-damaged conditions.